Propuesta de un modelo de un pozo horizontal con el fin de mejorar la eficiencia de producción en un campo de Ecopetrol S.A. (2018)
The research project is based on the statistical study of 28 horizontal wells with geosteering, including the drilling parameters and production in the wells, in order to identify the highest and lowest production efficiency. From the best wells, two proposals are shown for increasing the production of the two wells with the lowest productive performance. Finally, with the help of the software COMPASS, the trajectories with new sand targets (Zone 2), the drilling parameters, the geological characteristics and the good operational practices are presented in the proposals of the horizontal wells, result from previously mentioned statistical study and so improve the production efficiency in a field of Ecopetrol S.A.